2007
DOI: 10.1016/j.neuroscience.2007.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery in rats with ischemic paraplegia after spinal grafting of human spinal stem cells

Abstract: Transient spinal cord ischemia in humans can lead to the development of permanent paraplegia with prominent spasticity and rigidity. Histopathological analyses of spinal cords in animals with ischemic spastic paraplegia show a selective loss of small inhibitory interneurons in previously ischemic segments but with a continuing presence of ventral alpha-motoneurons and descending cortico-spinal and rubro-spinal projections. The aim of the present study was to examine the effect of human spinal stem cells (hSSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
86
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 44 publications
17
86
0
4
Order By: Relevance
“…More frequent measurements of individual patients are likely to identify ''noise'' that may not reflect true changes in disease progression. EIM, a newer and potentially more powerful biomarker of clinical progression, was performed at baseline for patients 1-6 and monthly for at least 3 months prior to surgery for patients [7][8][9][10][11][12]. The data are summarized in Figure 2, in which the major parameter, the 50 kHz phase averaged for all six muscles studied, for all 12 patients is plotted against time.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…More frequent measurements of individual patients are likely to identify ''noise'' that may not reflect true changes in disease progression. EIM, a newer and potentially more powerful biomarker of clinical progression, was performed at baseline for patients 1-6 and monthly for at least 3 months prior to surgery for patients [7][8][9][10][11][12]. The data are summarized in Figure 2, in which the major parameter, the 50 kHz phase averaged for all six muscles studied, for all 12 patients is plotted against time.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…These cells, expanded in serum-free media more than many passages, have shown therapeutic benefit when injected into the ventral horn area of spinal cord in the G93A rat model of familial ALS [7] and in a rat model of ischemic spinal cord injury [8]. In these motor neuron disease paradigms, the majority of the transplanted HSSCs differentiated into neuronal populations expressing glutamatergic and GABAergic neurotransmitter markers [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the loss of these specific inhibitory pools localized in the intermediate zone of the spinal grey matter, ultimately leads to an increase in the monosynaptic reflex and nearcomplete loss in spinal polysynaptic activity. A challenging study done in collaboration with anesthesiology research laboratory at University of California San Diego, has shown that NSCs derived from human fetal spinal cord grafted into a rat model of ischemic spastic paraplegia resulted into a progressive recovery of motor function with correlative improvement in motor evoked potentials (Cizkova et al 2007). Of note, transplanted NSCs became integrated into host neuronal circuits and displayed an extensive axo-dendritic outgrowth and active rostrocaudal/dorsoventral migration for about 8-12 weeks.…”
Section: Transplantation Strategies Utilizing Nscsmentioning
confidence: 99%
“…Patients who suffer from spinal cord trauma show limited functional recovery, which frequently leads to deficit of multiple sensory, motor and autonomic systems resulting to clinical signs of partial or complete paralysis with prominent spasticity and rigidity (Cizkova et al 2007). Because of the limited regenerative capacity of the adult CNS due to the inhibitory molecules, decrease of trophic factor support and scar tissue formation, the current functional treatments for SCI are not successful (Rowland et al 2008).…”
Section: Introductionmentioning
confidence: 99%